ICT ADOPTION AND USE IN TANZANIA SMEs - Msuya, Cuthbert A.; Mjema, Emanuel A. M.; Kundi, Beatus A. T. (Tanzania Journal of Engineering and Technology, 2018)
The purpose of this paper was to establish the status of ICTs adoption and use in Tanzania SMEs. Previously, it was shown that there is a shortage of comprehensive, accurate and up to date data on many aspects of the SMEs sector including the level of ICT adoption and use. This has affected government efforts aimed at development of this important sector in the economic development of the country. Results show that: (i) By year 2014, adoption of ICTs in SMEs had grown from almost non-existence in year 2004 to 80.1% computer technology use, and over 56.6% for use of internet technologies; (ii) More than 53% of the SMEs were using ICTs as a strategic communication and marketing tool; (iii) 47% of the SMEs were competitive due to use of ICTs. Given these results, the government and key stakeholders can formulate more effective policies and incentives aimed at developing the SME sector. Further research is recommended to address post adoption competitiveness issues. Key Words: ICT Adoption, SMEs, Competitiveness, Tanzania